2018
DOI: 10.1039/c8cp02768d
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic magnetic nanoparticles for biomedicine: bridging frequency separated AC-field controlled domains of actuation

Abstract: Magnetic nanoparticles constitute potential nanomedicine tools based on the possibility to obtain different responses (translation, rotation, heating, etc.) triggered by safe remote stimulus. However, such richness can be detrimental if the different performances are not accurately differentiatedand controlled. An example of this is the reorientation of magnetic nanoparticles under the influence of AC fields, which can be exploited for either magneto-mechanical actuation (MMA) at low frequencies (tens of Hz); … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…have been revised in detail to determine the transition between heat dissipative mechanisms and magneto-mechanical actuation. As a result, in viscous media the mechanical rotation induced by AMFs is mainly relevant for large MNPs (15–50 nm) and low frequency AMFs (<10 kHz) [ 63 , 64 ], although it can be exploited to exert effective mechanical torque on biological components [ 65 ]. This transition with AMF frequency becomes even clearer in the case of large anisometric NPs [ 63 ] and some empirical studies reported that AMFs induce a torque [ 66 ] or a physical movement of the MNPs [ 67 ] that may produce mechanical damage of the lysosome and cell membrane [ 68 , 69 ].…”
Section: Physical Concepts Of Magnetic Hyperthermia (Mh)mentioning
confidence: 99%
See 1 more Smart Citation
“…have been revised in detail to determine the transition between heat dissipative mechanisms and magneto-mechanical actuation. As a result, in viscous media the mechanical rotation induced by AMFs is mainly relevant for large MNPs (15–50 nm) and low frequency AMFs (<10 kHz) [ 63 , 64 ], although it can be exploited to exert effective mechanical torque on biological components [ 65 ]. This transition with AMF frequency becomes even clearer in the case of large anisometric NPs [ 63 ] and some empirical studies reported that AMFs induce a torque [ 66 ] or a physical movement of the MNPs [ 67 ] that may produce mechanical damage of the lysosome and cell membrane [ 68 , 69 ].…”
Section: Physical Concepts Of Magnetic Hyperthermia (Mh)mentioning
confidence: 99%
“…Magnetic materials tend to minimize their magnetic poles by locating their magnetization along their longest axis, establishing the geometrical easy magnetization axis. The geometric anisotropy can be enhanced by creating anisometric nanostructures like nanocubes, nanorods and nanodiscs [ 63 , 96 , 97 , 98 ]. These nanostructures are of general interest as they are good mechano-transducers that may apply large torques on biological components although they must be prepared with reduced dimensions to preserve their superparamagnetic response [ 99 , 100 ].…”
Section: Mnps For Mhtmentioning
confidence: 99%
“…While at low frequencies it was predicted that the disks absorbed energy and transformed it into particle rotational energy, at high frequencies the behaviour depended on the amplitude of the applied field: for large field amplitudes (greater than the switching field) the energy went into internal energy (heating), whereas for small field amplitudes the energy went into rotational motion. 14 On the other hand, it has been widely reported that the magnetization dynamics under an AC field are intimately associated with the influence of dipole interactions among MNPs, being able to either improve or worsen the hyperthermic response of MNPs. In this context, K. Simeonidis et al demonstrated that even if anisometric nano-spindles heat via Brownian relaxation (and such a contribution can be discarded as a heating mechanism in relevant media similar to that of tumours), the formation of their corresponding chains led to the heat dissipation by the Néel reversal mechanism (due to a progressive reorientation of the elongated structures during the AC treatment).…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic composite nanomaterials have been widely used in environmental protection, catalysis, and biomedicines and have broad application prospects. [25][26][27][28]. A large number of studies have been carried out on the removal of heavy metals in wastewater by using magnetic nanoparticles as magnetic core in the composite adsorption materials.…”
Section: Introductionmentioning
confidence: 99%